Respeitar, proteger, promover e prover: perspectivas sobre o direito humano à alimentação adequada (dhaa) na efetivação de políticas públicas em alimentação na atualidade - (:unkn) unknown (Universidade Federal do Pampa, 2022)
This paper seeks to discuss the inclusion of the Human Right to Adequate Food (DHAA) in Brazilian legislation and in its mechanisms of enforcement of food and nutritional security (SAN) through public policies and social programs, such as the National Food and Nutrition Policy (PNAN), the National Policy of Food and Nutritional Security (PNSAN) and the National Food and Nutritional Security Plan (PLANSAN) in the current days, having as a reference period the years from 2018 to 2021. As mechanisms of functioning and participatory effectiveness of the Human Right to Adequate Food, Brazil also counts with the Interministerial Chamber For Food and Nutrition Security (CAISAN) and, previously, the National Council for Food and Nutritional Security (CONSEA). Through bibliographic research for the presentation of the concepts that are transversal to this debate, and documentary research through the analysis of the Brazilian texts and the recent studies on the state of food and nutritional security, the presented objective is to instigate dialogues on the importance of the dimension of human rights, such as DHAA, as central in all phases of public policies. It is possible to observe that Brazil has the supporting structure for the realization of DHAA at the constitutional level and in social and food access programs, but these have been in decline due to the dismantling of CONSEA and the budgetary cuts of essential programs for the promotion of food and nutritional security. The difficulty of achieving full citizenship in face of the violation of DHAA and the need to transform the systemic model of food production and distribution is also pointed out. It is concluded that since the achievement of human rights is a structural problem, the realization of the DHAA must be taken as a permanent commitment by the State, which requires constant political will to achieve its full commitments.
Keywords: Direitos Humanos; Direito à alimentação; Política alimentar; Política Pública; Human rights; Right to food; CNPQ::CIENCIAS HUMANAS